PREPARATION AND IN VITRO PERFORMANCE EVALUATION OF EGG YOLK IMMUNOGLOBULIN-LOADED SODIUM ALGINATE/CHITOSAN/SODIUM ALGINATE MICROCAPSULES FOR FEEDING - Yuanming Jin; Haojie Lv; Chengdu Cui; Mingzhu Wang; Wu He; Lianhua Cui; Changguo Yan (Journal of Animal and Plant Sciences, 2024)
Egg yolk immunoglobulin (IgY) is valuable against intestinal infections, however, its activity will be affected by the gastrointestinal fluid of livestock and poultry and the storage environment. Therefore, we prepared IgY-loaded sodium alginate/chitosan/sodium alginate microcapsules (IgY-loaded SA/CS/SA MCs), aiming to improve the poor tolerance of IgY in the gastrointestinal tract of livestock and poultry as well as the instability of its storage performance, so as to improve the performance of its application. In this experiment, IgY was used as the core material, and sodium alginate and chitosan were used as the wall material, and the preparation was carried out by the extrusion method. The results showed that the encapsulation efficiency of the prepared IgY-loaded SA/CS/SA MCs was highest (94.84%) when the IgY concentration was 200 mg/mL, the CS concentration was 0.8%, and the CS solution pH value was 5.0(P<0.05). After freeze-drying, the shape of the MCs in group T1 was more regular, with an average particle size of 2.159 mm and the highest compressive strength (P<0.05). The stability of the T1 group in simulated gastric fluid (pH 2.0) was significantly enhanced compared to that of the NC, T2, and T3 groups (P<0.05),and theT3 group showed significantly improved antibacterial properties and increased alkalinephosphatase content compared to the T1 and T2 groups (P<0.05). In addition, IgY-loaded SA/CS/SA MCs were stored at room temperature (23±2°C) for 8 weeks, and the IgY activity in the T1 group was maintained at >70% (P<0.05). Therefore, the IgY-loaded SA/CS/SA MCs enhanced the tolerance and storage stability of IgY in simulated gastrointestinal fluids and showed significant inhibition of E. coli and SG in vitro.
Keywords: Egg yolk immunoglobulin; sodium alginate/chitosan/sodium alginate microcapsules; preparation process; in vitro evaluation